2018
DOI: 10.11648/j.ijde.20180302.12
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Comprehensive Diabetes Care (CDC) Management Program in Elderly Male Patients of Type II Diabetes Mellitus: A Retrospective Study

Abstract: Globally, Diabetes mellitus (DM) prevalence has created menace, being a major culprit of increased mortality and morbidity and health care expenditures. India is the 2 nd country with maximum number of diabetic patients, with an estimated prevalence of around 10%. Comprehensive Diabetes Care (CDC) is a combination of Panchakarma and Diet management. This study was conducted to evaluate the effect of CDC on glycosylated haemoglobin (HbA1c), body mass index (BMI), body weight, abdominal girth and dependency on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Basti. All these procedures acts by reducing glucose production in the liver by inhibit the process of gluconeogenesis, reduction in wear and tear of vascular endothelium, optimization of deranged lipid levels, etc [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Basti. All these procedures acts by reducing glucose production in the liver by inhibit the process of gluconeogenesis, reduction in wear and tear of vascular endothelium, optimization of deranged lipid levels, etc [10].…”
Section: Discussionmentioning
confidence: 99%
“…Swedana exposes the diabetic patients to high temperature of 40-42 degree Celsius through steam. Such passive heat therapy is postulated to sooth the patient and induce sweating, which get rid of excess of sodium and water load in diabetic patients, which maintains the vascular health and thus reducing the chances of vascular complications [10]. Basti is per rectal administration of herbal drugs like 40% Gudmaar (Gymnema sylvestre), 20% Daruharidra (Berberis aristate) and 40% Yashtimadhu (Glycyrrhiza glabra).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Sane et al reported decrease in HbA1c levels from 8.27±0.96 at day 1 to 7.1±1.30 at day 90. 8 Shingan et al documented a decrease in HbA1c levels from 7.87±1.90% to 5.79±0.51% at day 90. 9 Sane et al observed a decrease in HbA1lc levels from 9.02±1.79% to 6.86±1.24%.…”
Section: Diet Kit Consumptionmentioning
confidence: 96%